4‐4: High Stability Green Luminescent Microspheres based on Quantum Dot. Issue 1 (30th May 2018) - Yang, Lei; Lu, Rui; Hao, Junjie; Yang, Zhibin; Bian, Dun; Wu, Dan; Wang, Kai; Sun, Xiao Wei
Abstract : In this work, atomic layer deposition (ALD) technique was used as an efficient method to significantly improve the stability of green Quantum dots Luminescent Microspheres (QLuMiS) by depositing an alumina layer on the outer surface of QLuMiS. The composite microspheres based LED reveals long term stability and excellent light performance.